Hydrothermal synthesis of K+/Na+ codoped ZnWO4:Yb3+,Tm3+ nanophosphor for greatly enhanced NIR up-conversion luminescence - Li, Meiting; Wang, Xuejiao; Zhu, Qi; Li, Ji-Guang; Kim, Byung-Nam (Journal of Materials Research and Technology, 2021)
K+/Na+ doped ZnWO4:Yb3+,Tm3+ nanophosphors were successfully synthesized via malate assisted hydrothermal reaction at 180 °C for 24 h, followed by calcination at 700 °C for 2 h, and K+/Na+ incorporation was demonstrated to significantly affect the up-conversion (UC) and down-conversion (DC) luminescence of Tm3+. The best luminescent ZnWO4:0.08 Yb3+,0.02 Tm3+ phosphor, which contains ~4.8 at% of Na+ and 0.3 at% of K+, showed intensities ~11 and 20 times those of the phosphor containing only ~3 at% of Na+ for the 483 nm blue and 807 nm NIR UC, respectively, and has a much longer lifetime of ~468.10 ± 0.51 μs for the NIR emission. It was analyzed that the blue and NIR emissions occur via three- and two-photon processes, respectively, and have a high I807/I484 intensity ratio of ~185. Analysis of DC luminescence further confirmed the beneficial effect of K+/Na+ doping and found the co-presence of broad-band emission from [WO6]6- (3T1u → 1A1g transition, ~425–700 nm) and narrow-band emissions from Tm3+ (intra-4f12 transition, at 483, 619 and 653 nm). The effect of Na+/K+ was discussed with the observed UC/DC luminescence properties.